2022
DOI: 10.1155/2022/3127899
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Green Innovation and Enterprise Sustainable Development Performance Based on the SBM‐DEA Model

Abstract: Since the introduction of a low-carbon economy, corporate performance is no longer limited to the evaluation of internal economic benefits but has become the performance of corporate sustainable development, adding environmental and social factors. Now, the whole world is paying attention to low consumption and low emission. As the main economic pillar of society, the enterprise undertakes the biggest low-carbon task. In order to develop the economy in the longer term and meet the needs of society, enterprises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The green innovation undertaken by firms under pressure from government environmental concerns has a compensating effect (Rashid et al, 2018). If the green innovation activity offsets the cost, the firm is likely to undertake other R&D activities on this basis (Han, Li, et al, 2022). Green innovation has the characteristics of a long period, high investment, and high risks.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…The green innovation undertaken by firms under pressure from government environmental concerns has a compensating effect (Rashid et al, 2018). If the green innovation activity offsets the cost, the firm is likely to undertake other R&D activities on this basis (Han, Li, et al, 2022). Green innovation has the characteristics of a long period, high investment, and high risks.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%